Piecing Together Phenotypes of Brain Injury and Dysfunction in Obstructive Sleep Apnea - Veasey, Sigrid (Frontiers in Neurology, 2012)
Obstructive sleep apnea (OSA) is a highly prevalent condition that is associated with significant neurobehavioral impairments. Cognitive abnormalities identified in individuals with OSA include impaired verbal memory, planning, reasoning, vigilance, and mood. Therapy for OSA improves some but not all neurobehavioral outcomes, supporting a direct role for OSA in brain dysfunction and raising the question of irreversible injury from OSA. Recent clinical studies have refined the neurobehavioral, brain imaging, and electrophysiological characteristics of OSA, highlighting findings shared with aging and some unique to OSA. This review summarizes the cognitive, brain metabolic and structural, and peripheral nerve conduction changes observed in OSA that collectively provide a distinct phenotype of OSA brain injury and dysfunction. Findings in animal models of OSA provide insight into molecular mechanisms underlying OSA neuronal injury that can be related back to human neural injury and dysfunction. A comprehensive phenotype of brain function and injury in OSA is essential for advancing diagnosis, prevention, and treatment of this common disorder.